Manoeuvrability of vessels in inland waterways and safety of navigation. (3rd July 2021) - Solanki, Inderveer
ABSTRACT: A green and sustainable mode of transport, the inland waterway transport in India will see accelerated growth with the new Inland Vessels Act, 2021. This increased traffic growth in restricted waters will lead to economic, environmental, and safety challenges. Good manoeuvrability of inland vessels is critical to resolve these concerns. The world over, inefficient manoeuvring has resulted in several incidents which have affected the safety of navigation and maritime trade. Manoeuvrability of seagoing vessels must meet the minimum standards as per International Maritime Organization (IMO) Resolution MSC.137(76) and the MEPC1/Circ850/Rev.3 guidelines. In comparison, only a few countries, river commissions, and classification societies have specified criteria for navigation tests for inland vessels, and this does not include India. Manoeuvrability criteria and results of the tests are essential to facilitate the safe movement of vessels. This article discusses the results of full-scale manoeuvrability tests of inland vessels conducted by the author on India's national waterways and the Indo-Bangladesh Protocol route. It proposes manoeuvrability criteria for inland vessels plying in the inland waterways of India, including cross-regional protocol routes. The article also recommends measures to improve the safety of navigation in inland waters.